Gain-of-function of the 1-aminocyclopropane-1-carboxylate synthase gene ACS1G induces female flower development in cucumber gynoecy. Issue 2 (2nd December 2020) - Zhang, Huimin; Li, Shuai; Yang, Li; Cai, Guanghua; Chen, Huiming; Gao, Dongli; Lin, Tao; Cui, Qingzhi; Wang, Donghui; Li, Zheng; Cai, Run; Bai, Shunong; et al.
Abstract: Unisexual flowers provide a useful system for studying plant sex determination. In cucumber ( Cucumis sativus L.), three major Mendelian loci control unisexual flower development, Female ( F ), androecious [ a ; 1-aminocyclopropane-1-carboxylate ACC synthase 11, acs11 ], and Monoecious ( M ; ACS2 ), referred to here as the Female, Androecious, Monoecious (FAM) model, in combination with two genes, gynoecious ( g, the WIP family C2H2 zinc finger transcription factor gene WIP1 ) and the ethylene biosynthetic gene ACC oxidase 2 ( ACO2 ). The F locus, conferring gynoecy and the potential for increasing fruit yield, is defined by a 30.2-kb tandem duplication containing three genes. However, the gene that determines the Female phenotype, and its mechanism, remains unknown. Here, we created a set of mutants and revealed that ACS1G is responsible for gynoecy conferred by the F locus. The duplication resulted in ACS1G acquiring a new promoter and expression pattern; in plants carrying the F locus duplication, ACS1G is expressed early in floral bud development, where it functions with ACO2 to generate an ethylene burst. The resulting ethylene represses WIP1 and activates ACS2 to initiate gynoecy. This early ACS1G expression bypasses the need for ACS11 to produce ethylene, thereby establishing a dominant pathway for female floral development. Based on these findings, we propose a model for how these ethylene biosynthesis genes cooperate to control unisexual flower development in cucumber. Abstract : In the Female locus, which controls female flower development in cucumber, ACS1G acquired a new expression pattern that overlaps with ACO2, thus releasing ethylene and bypassing the need for ACS11 .